Financial education and consumers' willingness to change behavior - Swarn Chatterjee; Leslie Green-Pimentel; Pamela Turner (Investment Management and Financial Innovations, 2010)
This paper uses proprietary data comprising of 4,155 participants who attended financial education seminars conducted by a major U.S. consumer credit counseling agency in 2007. In this study, knowledge gained from attending the seminars is estimated using a multivariate regression model. Results indicate that those most likely to gain knowledge from attending the financial education seminars were respondents between 18 and 24 years of age, lower income groups and respondents who did not complete college. The findings of this study also reveal that the minority groups, women, and the less educated were more willing to seek further financial counseling and act on behavior changes after attending the seminar.
Keywords: D14; D03; 330; Financial Education; Behavioral Economics; Experimental Economics; Program Evaluation; Financial literacy; Behavioral economics; Experimental economics; Project network techniques